Effectiveness of Progressive Tax Reform in Mitigating Wealth Inequality: An Analysis of Tax Revenue Elasticity toward the Gini Ratio - Puji Rahayu (CV. Get Press Indonesia, 2026)
This research addresses the critical issue of wealth inequality within the multidimensional context of global and domestic fiscal policy. The study aims to evaluate the efficacy of Indonesia’s progressive tax reforms, specifically the introduction of the 35% marginal tax bracket under the Harmonization of Tax Regulations Law (UU HPP), in mitigating the national Gini Ratio. Utilizing a quantitative descriptive design with an econometric approach, the study analyzes annual secondary time‑series data from 2018 to 2024 sourced from Statistics Indonesia (BPS) and the Ministry of Finance. The analysis focuses on tax revenue elasticity (\(e\)) and multiple linear regression to determine the responsiveness of Personal Income Tax (PIT) relative to the national tax base and wealth distribution. Results indicate a buoyant tax system with an elasticity coefficient of 1.12 (), demonstrating that revenue growth outpaces economic expansion. However, despite increased fiscal collection, the Gini Ratio remains resistant to significant decline, fluctuating between 0.381 and 0.388. These findings imply a disconnect between revenue mobilization and actual redistribution, suggesting that wealth accumulation at the top decile outpaces current income tax corrective measures. The study concludes that while progressive rates are on the right trajectory, they must be augmented by direct wealth or capital gains taxes and integrated digital data systems to seal avoidance loopholes. Future research should prioritize the impact of luxury asset taxation on long‑term social equity.